Degradasi Moral dan Etika Bermedia Sosial dalam Film ‘Budi Pekerti’ - Fitriani, Annisa; Poedjadi, Maudy Rizkiana; Recky (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2024)
Film is an artistic expression that not only functions as entertainment, but also as a means of conveying moral messages and character building. This film, which was released on November 2 2023, carries a deep message. This film is the film